WORK PLACEMENT AFFECTS EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION - Suswati, Endang (Universitas Brawijaya, Indonesia, 2021)
The success of the banking industry in a crisis such as the Covid pandemic is highly dependent on employee performance. Employee performance in banking companies will increase employee efficiency and productivity. Employee performance improvement can be formed through accuracy in Work Placement and providing Work Motivation. Work Placement and employee motivation to improve performance are still debated in previous studies. Based on previous research gaps, this study aims to determine the effect of Work Placement and Work Motivation on Employee performance and to determine the effect of Work Placement on Employee performance through Work Motivation in employees of a government bank in Kediri, East Java, Indonesia. The number of respondents in this study was 58 people who were obtained by using the saturated sampling technique for employees. The data collection method used a questionnaire with PLS (Partial Least Square) analysis tool. The results of this study indicate that employee placement and work motivation influence the employee performance of a bank company. However, the Work Motivation variable as a moderating variable cannot be proven because there is no influence between the Work Placement variable on Work Motivation. The next researcher can retest and develop the concepts used in this research to contribute to the development and renewal of management science.